Digital-Based Customer Service Development Strategy in the Business Development Division of Merchant Marine in Indonesia - Suhartini Suhartini; Larsen Barasa; Aliya Izet Begovic Yahya (Greenation Research & Yayasan Global Resarch National, 2026)
Digital transformation in customer service is reshaping how educational institutions manage stakeholder engagement, yet systematic evidence from Indonesian maritime vocational institutions remains scarce. This study examines the digital-based customer service development strategies implemented by the Business Development Division of Sekolah Tinggi Ilmu Pelayaran (STIP) Jakarta, analyzing how five integrated digital tools web-based service platforms, AI-powered chatbots, WhatsApp customer service, Zoom consultations, and Google Forms satisfaction surveys collectively affect communication efficiency, responsiveness, and service quality. A qualitative case study design was employed, drawing on semi-structured interviews with 8 key informants from the Business Development Division, direct observation of digital tool deployment, and analysis of CRM logs and satisfaction survey data across one academic year. Data were analyzed through a systematic six-phase thematic analysis with intercoder verification (Cohen's Kappa κ = 0.82). The study's key findings reveal three interdependent success factors: technological infrastructure quality, staff digital literacy and training, and data-driven iteration and identify digital literacy constraints among customers as the most significant remaining implementation barrier. The principal theoretical contribution is a contextually grounded integration of SERVQUAL service quality dimensions (Parasuraman et al., 1988) with digital transformation theory within an Indonesian maritime higher education context the first such integration for this institutional type demonstrating that reliability and responsiveness dimensions of service quality are most substantially improved by AI chatbot and WhatsApp integration, while assurance and empathy dimensions are most effectively addressed through Zoom consultation. The findings provide maritime educational institutions with an evidence-based digital service integration model transferable across analogous vocational higher education contexts.